Presentation and Treatment of cholinergic Crisis in the setting of Carbamate poisoning. Issue 4 (23rd February 2021) - Nguyen, Hiep H.; Kidron, Ariel; Liu, Tianyi; Nguyen, Nghi; Nguyen, Hoang; Vo, An
Abstract: The case details the acute onset of muscarinic poisoning with associated symptoms and long‐term complications, as a new readily available suicide tool that clinicians should be keen to, combined with the appropriate treatment so lifesaving therapy may be urgently administered along with future mental health therapy.